Enamel Hypomineralization and Structural Defects in Amelotin-deficient Mice. (May 2015) - Nakayama, Y.; Holcroft, J.; Ganss, B.
Amelotin (AMTN) is a relatively recently discovered enamel protein that is predominantly expressed by ameloblasts during the maturation stage of amelogenesis and is present at lower levels in the junctional epithelium of erupted teeth. Previous studies have suggested a function of this protein in enamel mineralization and cell attachment. Genetic mouse models have been instrumental in defining the role of many enamel-related proteins, but a genetic mouse model lacking the Amtn gene has not been reported. Here, we describe the generation of amelotin-deficient mice and the analysis of their enamel phenotype in comparison with that of wild-type animals. Ablation of AMTN expression resulted in mechanically inferior enamel of mandibular incisors that showed chipping and fractures at the incisal edge. Enamel mineralization was delayed, resulting in hypomineralized inner enamel and structural defects in the outer enamel. Erupted enamel close to the gingival margin showed increased surface roughness. The expression levels of the enamel matrix proteins AMEL, AMBN, ENAM, and ODAM and the enamel proteases MMP-20 and KLK-4 were not significantly altered, although the expression of KLK-4 was delayed. The morphology of ameloblasts showing prominent Tomes' processes during the secretory stage was not altered, and there was no indication of disruption of cell structures or activities, but a residual layer, presumably consisting of organic material, remained at the enamel surface close to the gingival margin. The integrity of the dentogingival attachment at the junctional epithelium appeared unaffected by AMTN deficiency. These observations indicate that AMTN plays a subtle yet critical role in enamel biomineralization, particularly during the establishment of the outer and surface enamel layers. This role appears to be largely independent of other enamel proteins.